Correlation of the Concepts of “Legal Culture” and “Legal Mentality” - N. L. Orekhova (Теоретическая и прикладная юриспруденция)
The article contains a theoretical and methodological analysis of the structure and typology of legal culture as a social phenomenon. Particular attention is paid to discussion issues, the author compares the various positions of modern scholars on this issue, explores the varieties and social forms of legal culture. The article attempts to scientifically analyze the elemental composition of the legal culture: legal mentality and legal consciousness, legal activity and legal acts.